Estimation of genetic parameters in hybrid and F2 generations of aromatic fine rice for breeding improvement - Tareque, Abu Musa Md Main Uddin; Hassan, Lutful; Habib, Muhammad Ashraful; Nayak, Swati; Robin, Arif Hasan Khan (Springer, 2025)
"Background Genetic improvement in aromatic rice is crucial for enhancing its yield, quality, and resilience to environmental stressors. The present study was designed to analyze genetic parameters, heterosis, and inbreeding depression in F1 and F2 generations obtained from a crossing between fine and aromatic rice genotypes- Kataribhog and BRRI dhan50. Results A significant amount of variation was found from the analysis of variance among the genotypes of F1, F2, and their parents. Grain yield plant-1 showed a significant positive correlation with the number of tillers hill-1, number of effective tillers hill-1, flagleaf length, panicle length, grains panicle-1, filled grains panicle-1, and grain yield panicle-1. For all the traits of F1 and F2, the phenotypic coefficient of variation (PCV) was greater than the corresponding genotypic coefficient of variation (GCV), suggesting an influence of environment on the expression of these traits. Furthermore, high heritability along with high genetic advance as percentage of the mean (GAM) was observed for all the traits studied except days to first flowering and plant height in F1 and for grains panicle-1, filled grains panicle-1, grain yield panicle-1, and grain yield plant-1 in F2 generations which is an indication of additive gene control and selection for improvement could be effective. Both the cross and reciprocal cross had significant positive heterosis with subsequent inbreeding depression predominantly in the number of tillers hill-1, grains panicle-1, filled grains panicle-1, grain yield panicle-1, and grain yield plant-1, excluding days to first flowering suggested the scope for exploitation of heterosis. A higher estimate of transgressive segregation for grain yield plant-1 encouraged further breeding efforts. Conclusions This study highlights the potential for developing high-yielding aromatic rice through hybridization and selection. The observed genetic variation, high heritability, and heterosis confirm opportunities for yield improvement. By advancing segregating generations and integrating modern breeding tools, these findings pave the way for developing superior aromatic rice varieties with enhanced productivity and grain quality."